Pengaruh Persepsi Resiko dan Kelompok Referensi Terhadap Minat Beli Ayam Broiler Di Aceh Barat - Nurleili, Nurleili (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze and evaluate the effect of Risk Perception (X₁) and Reference Group (X₂) on Purchase Intention (Y) for Broiler Chicken in West Aceh, both partially and simultaneously. The research employed a quantitative approach with a descriptive research design. The population in this study consisted of all consumers of Broiler Chicken in West Aceh Regency. Primary data were obtained through questionnaires and analyzed using multiple linear regression with the assistance of statistical software. The findings indicate that the Risk Perception variable (X₁) has a significant influence on the purchase intention of Broiler Chicken in West Aceh, with a significance value of 0.010 < 0.05. The positive regression coefficient of 0.157 suggests that when consumers have a clear understanding and feel that potential risks (such as health or food safety) can be managed or minimized, their purchase intention increases. Meanwhile, the Reference Group variable (X₂) also shows a significant and dominant effect on purchase intention (Y), with a significance value of 0.000 < 0.05. The regression coefficient of 0.535 indicates a stronger positive effect compared to risk perception, meaning that more positive recommendations and influences from family, friends, or close acquaintances lead to higher consumer purchase intention. Simultaneously, Risk Perception and Reference Group significantly influence the purchase intention of Broiler Chicken, as evidenced by an F-test significance value of 0.000 < 0.05. The coefficient of determination (R²) of 0.542 indicates that 54.2% of the variation in purchase intention can be explained by the two independent variables, while the remaining 45.8% is influenced by other factors not examined in this study. Thus, it can be concluded that the Reference Group is the most dominant factor shaping consumers’ purchase intention for Broiler Chicken in West Aceh.